Assessment of mobile phone problematic usage and associated health related symptoms among medical students at Goa Medical College - Bhamaikar, Varsha M.; Bicholkar, Abhishek; Cacodcar, Jagadish (International Journal Of Community Medicine And Public Health, 2019)
Background: Mobile Phones can be considered as one of the essential socio-personal utility with diverse features but its overuse may have negative consequences on health. The objective of the present study was to assess the prevalence of mobile phone problematic usage among the medical students and to study the association of health related symptoms and problematic mobile phone usage. Methods: A total of 250 medical students were included in this study. Data regarding the sociodemographic factors and perceived health symptoms related to mobile phone use was collected on a predesigned, structured and self-administered questionnaire. Mobile phone problem use scale (MPPUS) was employed to assess the problematic usage of mobile phone and students were classified into following four categories - casual users (<74), regular users (75-143), at risk users (>143-<179) and problematic users (>179). Results: The total prevalence of problematic users was 22% (17.2% at risk, 4.8% problematic users). Eye strain, concentration difficulties, memory disturbances, morning tiredness, headache, sleep disturbances, painful fingers and restlessness were significantly associated with at risk and problematic users. Conclusions: Multiple health symptoms were associated with problematic use of mobile phones among the medical students. MPPUS is a useful tool which can be used to identify problematic usage of mobile phones.